2013
DOI: 10.1074/jbc.m113.510966
|View full text |Cite
|
Sign up to set email alerts
|

Arginine Residues on the Opposite Side of the Active Site Stimulate the Catalysis of Ribosome Depurination by Ricin A Chain by Interacting with the P-protein Stalk

Abstract: Background: Ricin A chain (RTA) uses the ribosomal stalk to access the sarcin/ricin loop (SRL). Results: Arginine residues at the interface of RTB are critical for RTA to bind to the stalk and to stimulate depurination of the SRL. Conclusion: Stalk binding stimulates depurination by orienting RTA toward the SRL. Significance: We propose a model that describes how RTA accesses the SRL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
113
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(122 citation statements)
references
References 69 publications
(100 reference statements)
7
113
1
Order By: Relevance
“…In RTA, at least two arginines had to be mutated in order to perturb the interaction between the toxin and the stalk pentamer or the ribosome before a reduction in toxicity was observed (28). Similarly, in TCS, single point mutations reduced the interaction with the P2 protein while a triple mutation disrupted the interaction (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In RTA, at least two arginines had to be mutated in order to perturb the interaction between the toxin and the stalk pentamer or the ribosome before a reduction in toxicity was observed (28). Similarly, in TCS, single point mutations reduced the interaction with the P2 protein while a triple mutation disrupted the interaction (12).…”
Section: Discussionmentioning
confidence: 99%
“…We recently showed that Stx2A1 has a higher affinity for the ribosome and higher catalytic activity and toxicity than Stx1A1 in both yeast and mammalian cells (26). The interaction of RTA with the ribosome depended on electrostatic interactions and followed a two-step binding model, where the slower, non-stalk-dependent electrostatic interactions concentrated RTA molecules on the ribosome and allowed the faster electrostatic interactions with the stalk P-proteins (27,28). Analysis of the electrostatic surface of the A1 subunits revealed differences in charge distribution around the active site and on the distal face of the active site in a region shown to be important for the interaction of Stx1A1 with the P11 peptide (26).…”
mentioning
confidence: 99%
“…Total RNA (1 g) was incubated with different concentrations of Stx1A1 and Stx2A1 (62.5 nM, 125 nM, and 250 nM) in a final volume of 20 l in 20 mM citrate buffer (pH 5) at 37°C for 15 min. RNA was purified (43), and the depurination of rRNA was quantified by using a qRT-PCR assay (42). The ⌬⌬C T method was used to calculate the depurination level, and data were expressed as the fold change of depurination in Stx-treated RNA over depurination in nontreated RNA, as described previously (40,42).…”
Section: Methodsmentioning
confidence: 99%
“…One hundred microliters of 2ϫ extraction buffer (120 mM NaCl, 25 mM Tris-HCl [pH 8.8], 10 mM EDTA, 1% SDS) was added to this mixture, and the mixture was vortexed. RNA was extracted from this mixture (43), and depurination was determined by using qRT-PCR (42).…”
Section: Methodsmentioning
confidence: 99%
“…Higher plants have a RPP1 and RPP2 family, as well as a third acidic RP called RPP3 (Szick et al, 1998;Chang et al, 2005). This stalk structure promotes eEF2 binding and GTP hydrolysis in yeast (Gonzalo and Reboud, 2003) and is important in the binding of ribosome inactivating proteins, such as the ricin toxin (Li et al, 2013c).…”
Section: Cytosolic Ribosomal Proteinsmentioning
confidence: 99%